Convergence culture : where old and new media collide - Jenkins, Henry, 1958- (ACLS Humanities E-Book., 2006)
Media analyst Jenkins delves beneath the new media hype to uncover the important cultural transformations that are taking place as media converge. He takes us into the secret world of Survivor Spoilers, where avid internet users pool their knowledge to unearth the show's secrets before they are revealed on the air. He shows us how The Matrix has pushed transmedia storytelling to new levels, creating a fictional world where consumers track down bits of the story across multiple media channels. Jenkins argues that struggles over convergence will redefine the face of American popular culture: industry leaders see opportunities to direct content across many channels to increase revenue and broaden markets; at the same time, consumers envision a liberated public sphere, free of network controls. Jenkins explains the cultural shift as consumers fight for control across disparate channels, changing the way we do business, elect our leaders, and educate our children.--From publisher description.